Is Bitcoin a Safe Haven? A Study on the Factors that Affect Bitcoin Prices - Gozbasi, Onur; Altinoz, Buket; Sahin, Eyup Ensar (International Journal of Economics and Financial Issues, 2021)
Bitcoin and other digital currencies are financial assets with high volatility, which calls for an investigation of the factors that influence their prices and thus has led to a debate on whether they are reliable investment instruments or diversification tools. The present study aims to explore the impact upon Bitcoin prices of commodities such as gold and oil, the S&P 500 index, and the volatility index and financial stress index, which represent the financial risk environment. To this purpose, we analyze this relationship using the Autoregressive Distributed Lag (ARDL) approach based on the monthly data from the 2010-2021 period. The results suggest that both in the long and short run, gold price per ounce does not have a statistically significant effect on Bitcoin price. On the other hand, an increase in crude oil prices has a negative impact on Bitcoin price in the short run, with no significant effect in the long run. The S&P 500 stock market index positively affects the Bitcoin price both in the short and long run. In addition, our analysis results also demonstrate that developments indicating increased risk in the long run tend to reduce Bitcoin returns. Keywords: Bitcoin, gold, oil, volatility, ARDL. JEL Classifications: G11; B23 DOI: https://doi.org/10.32479/ijefi.11602